ECOSUFISM IN SERAT CENTHINI AND ITS ACTUALIZATION: A THEOLOGICAL ANALYSIS OF THE HUMAN–NATURE–GOD RELATIONSHIP IN THE JAVANESE SUFI TRADITION: Case Study: Hifdzu Bi’ah Programme, Desa Ngantru) - Panji Nur Muhammad Sholih; Mauluddin Rahmat; Muhammad Ahsin Maulana; Abdurrahman Sholeh (Jurnal Studi Pesantren, 2026)
This study examines the dimension of ecosufism embedded within Serat Centhini through the lens of Islamic philosophy and theology, and investigates its actualization in contemporary environmental practice through a case study of the Hifdzu Bi’ah programme conducted by KKN-T students of Universitas Al-Qolam Malang in Desa Ngantru, Kecamatan Ngantang, Kabupaten Malang (2025). Employing Gadamer’s philosophical hermeneutics for primary textual analysis of Serat Centhini and document content analysis of the KKN-T field report as empirical data, the study yields three principal findings. First, Serat Centhini contains a robust proto-ecosufist foundation grounded in the doctrine of wahdat al-wujud expressed through manunggaling kawulo-Gusti, the concept of khalifah, and the Javanese cosmic ethic Memayu Hayuning Bawana. Second, these classical values exhibit significant theological continuity with contemporary ecosufism frameworks articulated by Nasr (1996) and Suwito (2014), while also undergoing productive transformations at the methodological and institutional levels. Third, the Hifdzu Bi’ah programme demonstrates that Serat Centhini’s ecosufist values can be operationalized through participatory Islamic community forums, particularly through the Fatayat and Muslimat NU women’s religious networks, although structural challenges including the absence of permanent institutional arrangements continue to limit long-term sustainability. This research contributes to the development of a Nusantara ecosufism model that bridges classical Islamic-Javanese intellectual heritage with pressing contemporary ecological challenges, offering an authentically local foundation for Islamic environmental theology in Indonesia.